2000
DOI: 10.1034/j.1600-051x.2000.027002134.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of oral irrigation for periodontitis are related to reduction of pro‐inflammatory cytokine levels and plaque

Abstract: Oral irrigation with water for 14 days had an improved therapeutic benefit for AP over that of routine oral hygiene alone and this improvement was accompanied by a down-modulation of the pro-inflammatory cytokine profile in GCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 18 publications
6
83
0
3
Order By: Relevance
“…Initial studies (not shown) established the dilution of test samples that yielded sufficient volume and sensitivity for detection of the four cytokines within the linear range of their respective standard curves (32). Dilutions ranged from 1/2.5 to 1/5 v/v.…”
Section: Analysis Of Gcf Cytokines By Elisamentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies (not shown) established the dilution of test samples that yielded sufficient volume and sensitivity for detection of the four cytokines within the linear range of their respective standard curves (32). Dilutions ranged from 1/2.5 to 1/5 v/v.…”
Section: Analysis Of Gcf Cytokines By Elisamentioning
confidence: 99%
“…Sections were stained with H&E to confirm the clinical diagnosis by histological means (not shown). The experimental design for the induction of active (n ϭ 12) or "quiescent" (n ϭ 20) gingival inflammation (Table I) in subjects with preexisting mild CP (minimum of three probing pocket depths of Ն 5 mm, clinical attachment levels of Ն 5 mm, bleeding on probing, and horizontal bone loss at the same sites), as well as the technique for sampling gingival crevicular fluid (GCF), have been described previously (32). All four periopaper strips from each tooth were placed in one glass screw-capped vial and stored at Ϫ80°C.…”
Section: Collection and Handling Of Clinical Specimens Disease Categmentioning
confidence: 99%
See 1 more Smart Citation
“…Actions focused exclusively on the tooth surface, associated plaque and invading bacterium can indeed reduce pro-inflammatory cytokine levels in crevicular fluid [15]. However, non-compliance -poor sustained oral hygiene regimen and missed returns for regular professional maintenance care -heavily influence undesirable therapeutic outcomes.…”
Section: Targeting Plaque -Current Tools Of Soft Tissue Managementmentioning
confidence: 99%
“…The excess formation of prostaglandin E 2 (PGE 2 ) has been described in a number of conditions characterized by increased susceptibility to infection, rheumatoid arthritis and inflammation, including periodontal diseases (8,17,25,29). PGE 2 mediates its biological functions via binding to four types of membrane-bound, G protein-coupled receptors, termed E prostanoid (EP)1 to EP4 (6, 22).…”
Section: Introductionmentioning
confidence: 99%